The Embodied Self, the Pattern Theory of Self, and the Predictive Mind - Newen, Albert (Frontiers in Psychology, 2018)
Do we have to presuppose a self to account for human self-consciousness? If so, how should we characterize the self? These questions are discussed in the context of two alternatives, i.e. the no-self position held by Metzinger (2003, 2009) and the claim that the only self we have to presuppose is a narrative self (Dennett 1992; Hardcastle 2008; Schechtman 2007) which is primarily an abstract entity. In contrast to these theories, I argue that we have to presuppose an embodied self, although this is not a metaphysical substance, nor an entity for which stable necessary and jointly sufficient conditions can be given. Self-consciousness results from an integration of an embodied, basic affective flow with an intentional object (the self as agent or as center of imagination or thought), where this integration remains anchored in an embodied self. This embodied self is a flexible and variable entity, which we can account for only with a pattern theory of the self (in line with Gallagher 2013). Furthermore, I outline how this pattern theory of the self fits into the predictive coding framework, which also answers the open question whether self-representation is prior to world-representation or the other way around. The principal organization of a mechanism of building up a self-model is such that both types of representations are always activated and developed in parallel. Modelling oneself is a process which is always activated when one interacts with the world – much as a shadow is present when a person walks in the sun.